MODEL FOR OPTIMIZING PRODUCTION COSTS USING MONTE CARLO SIMULATION IN SMES - Antonov, Anton (E-Journal VFU, 2025)
This article presents an easily accessible automated model for optimizing production costs in SMEs using Monte Carlo simulation. In the past such a model required entire departments full of employees and specialized server hardware to collect all the necessary data. Due to the development of the new technologies, personal computers and electronic databases, literally every entrepreneur is now able to use such simulation models. The key is appropriate selection of data input that the model can use to create a forecast that enables management to make informed decisions for more efficient use of all available resources in SMEs in the process of producing the desired goods.